OPTIMIZING CULTURE CONDITION FOR EXPRESSION OF CYP124 IN ESCHERICHIA COLI USING RESPONSE SURFACE METHODOLOGY APPROACH - Marta Gunawan, Catherine
Metabolic engineering in bacteria can produce heterologous secondary metabolites. Therefore, Mycobacterium tuberculosis can hydroxylate farnesyl pyrophosphate (FPP) at C?produce 12OH-FPP. Hydroxylated FPP is precursor for amorphadiene synthase (ADS) producing dihydroartemisinic acid so biosynthetic steps on artemisinin production can be reduced. Optimization of CYP124 expression was carried out using Response Surface Methodology by varying FeCl3, 5-ALA, and IPTG concentration in medium. The parameters measured from this treatment were R/Z, CYP124 mass from SDS-PAGE results, and CYP124 characterization. SDS-PAGE purified CYP124 showed a single band around 45 kDa. Factor affecting CYP mass is interaction IPTG and 5-ALA. 5-ALA also affecting R/Z value. Validation for optimal design result was match with the predicted CYP mass and R/Z value. So, optimal design for CYP124 expression is addition 0.10 mM FeCl3, 1 mM 5-ALA, and 0.2427 mM IPTG. To ensure that produce CYP124 enzyme is functional, an activity assay can be carried out.